FOREIGN POLICY AND DIPLOMATIC RELATIONS DURING THE REIGN OF MIRZO ULUGBEK (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the foreign policy and diplomatic relations during the reign of Mirzo Ulugbek, a prominent figure of the Timurid Renaissance, ruler, and encyclopedic scholar. Following the political transitions after Amir Temur’s death, the restoration and development of diplomatic, trade, and economic relations with neighboring countries–specifically China, India, Tibet, Egypt, and the Ottoman Empire–under Shahrukh Mirza and Mirzo Ulugbek are examined. Based on the provided lecture materials, the article highlights the unique pragmatic aspects of Ulugbek’s diplomacy, the exchange of trade caravans along the Great Silk Road, and the role of cultural and scientific diplomacy.
Keywords: Mirzo Ulugbek; Timurid diplomacy; Mavarannahr; China (Dai Ming); Great Silk Road; embassy relations; Abdurazzak Samarkandi; cultural diplomacy